Gerakan Sikat Gigi Sejak Dini: Edukasi Pencegahan Caries Gigi untuk Mencegah Stunting Pada Anak Usia Sekolah di SD Negeri 83 Seluma, Desa Sukasari Kec. Air Periukan Kab. Seluma Prov. Bengkulu - Merita, Nina; Aprianti , Heni Dyah; Elisabet , Maria Natalia; Nurjanah , Nimas Ayu Lestari; Yulianti , Syami (Jurnal Pengabdian Mitra Persada, 2025)
Oral health problems, particularly dental caries (tooth decay), are common among elementary school children and can contribute to stunting. Untreated caries can interfere with children’s nutritional intake due to pain while eating, which in the long term may affect growth. This activity aimed to provide education on the importance of maintaining dental health to prevent caries through a practice-based educational approach. The methods used included oral health education, a ±3-minute educational video on proper tooth brushing techniques, and a live demonstration involving teachers, university students, and a local dentist. The activity was conducted on May 9, 2025, at SD Negeri 83 Seluma, Sukasari Village, Air Periukan Subdistrict, Seluma Regency, Bengkulu Province, involving 62 students from grades 3 and 4. Observations showed that students were able to follow the activities and practice proper tooth brushing techniques. In conclusion, this educational program provided meaningful hands-on experience in promoting oral hygiene habits from an early age and is expected to serve as a promotive-preventive education model applicable to other elementary schools.